A Study on Violation of Sections 4 and 6 of the Cigarettes and Other Tobacco Products Act (COTPA) 2003 in Chennai, Tamil Nadu - .E, Sathishkumar (International Journal of Psychosocial Rehabilitation, 2020)
According to the World Health Organization (WHO), there are 246 million smokers and 290 million smokeless tobacco users in the South-East Asian region, which is considered one of the largest tobacco consuming regions. India is the second-largest consumer and third largest producer of tobacco. Nearly twenty-eight percent of adults in India consume smoke or smokeless form of tobacco. Tobacco consumption is a major cause of non-communicable diseases like lung diseases, cancer, and cardiovascular diseases. In India, “The Cigarettes and Other Tobacco Products Act (COTPA) 2003” are implemented throughout the country, which contains a smokefree environment, the prohibition of advertising, bans the promotion of tobacco products, the prohibition of sales of tobacco to minors and statutory warnings. Tamil Nadu government has taken various health policy initiatives to control the use of tobacco products and create awareness among the users. However, still people are tried to violate the laws. The nature of the study is to analyze the number of violations of Sections 4 and 6 of Cigarettes and Other Tobacco Products Act 2003, from 2016 to 2019 in Tamil Nadu. Also, examine the violation of Sections 4 and 6 of COTPA 2003 in Chennai from 2008 to 2019.